2022
DOI: 10.1007/s10869-022-09810-6
|View full text |Cite
|
Sign up to set email alerts
|

How Can Organizational Leaders Help? Examining the Effectiveness of Leaders’ Support During a Crisis

Abstract: Organizational leaders can make a large, positive impact on their employees during crises. However, existing research demonstrates that social support is not always effective in helping employees cope with stress, and existing research has not fully identified features of support attempts that determine their effectiveness. Using mixed methods, the authors investigate the efficacy of organizational leaders’ support efforts during a crisis. In the first study, 571 employees (196 university administrative staff,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
18
0
5
Order By: Relevance
“…Also Mihalache and Mihalache ( 2022 ) noted that supervisor accessibility is one of the support forms that can help with uncertainty during the pandemic and increase affective commitment. Gray et al ( 2022 , in press), however, noted that not all attempted support behavior is actually helpful and identified nine themes that should be considered for reasonable support during crises, namely autonomy, communication, changes, personal resources, safety, time, tone, work equipment, and workload.…”
Section: Discussionmentioning
confidence: 99%
“…Also Mihalache and Mihalache ( 2022 ) noted that supervisor accessibility is one of the support forms that can help with uncertainty during the pandemic and increase affective commitment. Gray et al ( 2022 , in press), however, noted that not all attempted support behavior is actually helpful and identified nine themes that should be considered for reasonable support during crises, namely autonomy, communication, changes, personal resources, safety, time, tone, work equipment, and workload.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that organizational leaders can have a large, positive impact on their employees during crises. 26 It is the team leader's responsibility to provide clear communication, access to adequate personal protection and adequate rest. 27 Furthermore, to protect health care providers, initiatives at the national professional society level can also help, including (1) acknowledging and regularly measuring the extent of burnout, (2) establishing professional wellness programs such as resilience courses, and (3) educating and advocating through social media as well as plenary sessions at national meetings.…”
Section: Discussionmentioning
confidence: 99%
“…The Impact of Events Scale-Revised (IES-R) has been proven to be suitable for the Chinese population, 13 and it was incorporated to evaluate the psychological impact of COVID-19. It is a 5-point Likert scale for which the total scores can be categorized into 4 different levels: subclinical (0-8), mild (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), and severe (44-88). Scoring above the threshold of 33 was considered diagnostic of PTSD.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…At best, monitoring is a nuisance. During the pandemic, employees perceived employers who sent too many emails or required extra timesheets to be unhelpful (Gray et al., 2020). Over the long run, monitoring damages the quality of employment relationships.…”
Section: Workplaces In the Next Normal: A World Of Possibilitymentioning
confidence: 99%